Development of power converters for grid integration of solar energy (part – 2) - Handy. (2009)
In this report, the use of Z-source inverter will be discussed as an alternative to the traditional two-stage DC/DC and DC/AC power converters. The Z-source inverter comprises of inductors and capacitors, thus allowing both buck and boost effects. Maximum power point tracking (MPPT) is used in photovoltaic (PV) systems to maximize the photovoltaic array output power, irrespective of the temperature and irradiation conditions and of the load electrical characteristics. The resulting system has high-efficiency, lower-cost and can be easily modified to handle more energy sources (e.g. wind-generators). For the system to track the Maximum Power Point, unified control technique is used. In the unified control technique, the Z-source will operate in optimum to give the maximum power. The output ac voltage and current will be sensed and feedback to the system to maintain the output voltage level and frequency. With the voltage and current sensed, output power and ΔP can be calculated in the program. The objective of this project is to convert the solar panel output to a three phase output with the voltage level and frequency the same as grid and to prove the capability of Z-source network to replace the traditional two-stage VSI and DC/DC converter. The grid voltage is 230Vac, with a frequency of 50Hz and balanced three-phase with 120° phase difference.